Cultivable bacterial community from the rhizosheath of Amaranthus hypochondriacus - Ferrara-Guerrero, María Jesús (REVISTA TERRA LATINOAMERICANA, 2013)
Amaranth (Amaranthus hypochondriacus L.) is a plant species that tolerates the semiarid conditions prevailing in sandy soils in the central Valley Mexico region. In spite of its agronomic relevance, there is a lack of information about the soil-plant-microbe interactions in this plant species. The aim of this research was to study the phenotypic changes of the bacterial community considering physiological and biochemical traits, as well as its contribution to the delivery of available nutrients, in the rhizosheath of amaranth cultivated in a sandy soil in the Valley of Mexico. Rhizosheath soil samples were extracted at four stages of the crop plant (seeding, flowering, harvest and postharvest); 38 bacterial isolates were purified and characterized following 8 physiological and 34 biochemical tests. The results revealed high heterotrophic potential in the bacterial community. A cluster analysis and the index of similarity and Euclidean distance of Ward considering all physiological and biochemical applied tests, grouped the 38 isolates in 3 phenons, one pair and one isolate alone. This analysis and its comparison with general descriptions contained in the Bergey's Manual revealed that bacterial isolates belong to the Bacillaceae, Enterobacteriaceae, Pseudomonadaceae and Streptomycetaceae Families. In relation to their capacity of degradation, the bacterial isolates from harvest and postharvest stages showed the highest production of the extracellular enzymes DNase, chitinase, phosphatase and esculinase. Finally, the potential for agricultural biotechnology of bacterial isolates from the rhizosheath of amaranth is emphasized.